2018
DOI: 10.1111/cas.13874
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 expression enhancement by infiltrating macrophage‐derived tumor necrosis factor‐α leads to poor pancreatic cancer prognosis

Abstract: Immunotherapy using anti‐PD‐1/PD‐L1 antibodies for several types of cancer has received considerable attention in recent decades. However, the molecular mechanism underlying PD‐L1 expression in pancreatic ductal adenocarcinoma (PDAC) cells has not been clearly elucidated. We investigated the clinical significance and regulatory mechanism of PD‐L1 expression in PDAC cells. Among the various cytokines tested, tumor necrosis factor (TNF)‐α upregulated PD‐L1 expression in PDAC cells through NF‐κB signaling. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 39 publications
(77 reference statements)
1
39
1
Order By: Relevance
“…In addition to these extrinsic stimuli, intrinsic genetic alteration such as PD‐L1 gene amplification and deletion of the 3′‐UTR may influence PD‐L1 expression . We previously found that there was a significant correlation between PD‐L1 expression in cancer cells and macrophage infiltration in the tumor microenvironment, and macrophage‐derived tumor necrosis factor‐α was revealed to induce PD‐L1 overexpression via NF‐κB signal activation in pancreatic cancer . In the present study, macrophage infiltration was also detected by Iba‐1 IHC as described previously .…”
Section: Discussionmentioning
confidence: 56%
“…In addition to these extrinsic stimuli, intrinsic genetic alteration such as PD‐L1 gene amplification and deletion of the 3′‐UTR may influence PD‐L1 expression . We previously found that there was a significant correlation between PD‐L1 expression in cancer cells and macrophage infiltration in the tumor microenvironment, and macrophage‐derived tumor necrosis factor‐α was revealed to induce PD‐L1 overexpression via NF‐κB signal activation in pancreatic cancer . In the present study, macrophage infiltration was also detected by Iba‐1 IHC as described previously .…”
Section: Discussionmentioning
confidence: 56%
“…TAM are known to show an immunosuppressive phenotype by attracting other immunosuppressive cells such as regulatory T cells, myeloid‐derived suppressor cells and type 2 helper T cells . Recently, TAM infiltration has been reported to be associated with the upregulation of PD‐L1 expression in gastric and pancreatic cancer, but its molecular mechanism is limited. The present study is the first report describing the association between TAM infiltration and tumor PD‐L1 expression in early lung AC, and to further show that TAM induced PD‐L1 expression on tumor cells via TGF‐β using an in vitro co–culture system.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to different mechanisms of PD‐L1 induction by macrophages in cancer cells. It has also been reported that tumor PD‐L1 expression is enhanced by TNF‐α from TAM in pancreatic cancer and NF‐κB signal elicited by macrophage inflammatory responses, including production of TNF‐α and IL‐1β, can trigger PD‐L1 expression in hepatocellular carcinoma cells . In this study, we identified TGF‐β as an additional key inducer of PD‐L1 in both A549 and H1975 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanism of PD‐L1 regulation in pancreatic cancer has not been elucidated fully. Existing reports show that tumor necrosis factor‐α, secreted by macrophages, increases PD‐L1 expression in pancreatic cancer . Previously, we found that the RB–p65 axis , FUBP1–Myc axis , HAT1–BRD4 axis or HDAC3 regulated PD‐L1 expression in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 68%